1977
DOI: 10.1007/bf02532976
|View full text |Cite
|
Sign up to set email alerts
|

2‐Aminoethylphosphonic acid metabolism in the rat

Abstract: Time course studies of the incorporation of radioactive 2-aminoethylphosphonic acid (AEP) into the tissues of rats demonstrated that maximum incorporation into the liver lipids occurred within 12 to 30 hr after injection, compared to 2 to 3 hr for the incorporation of phosphorylethanolamine. Little incorporation of AEP was observed in the other tissues investigated (heart, lung, spleen, adipose, kidney). The AEP was incorporated to the greatest extent into 1,2-diacylglyceryl-aminoethylphosphonate (diacylglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that 2-AEP is detected in the goat liver, bovine brain and liver, and major tissues of rats, chicken, and humans, including skeletal muscle [59,60]. In the rat liver, 2-AEP is incorporated in phosphonolipids, such as diacylglyceryl-AEP [61], which suggests that 2-AEP is a membrane component. Thus, 2-AEP in the bovine fetus may be taken up from the pregnant cows through the placenta and utilized as a membrane component.…”
Section: Other Metabolites Altered In the Fetal Muscles Of The Ln Groupmentioning
confidence: 99%
“…Previous studies have reported that 2-AEP is detected in the goat liver, bovine brain and liver, and major tissues of rats, chicken, and humans, including skeletal muscle [59,60]. In the rat liver, 2-AEP is incorporated in phosphonolipids, such as diacylglyceryl-AEP [61], which suggests that 2-AEP is a membrane component. Thus, 2-AEP in the bovine fetus may be taken up from the pregnant cows through the placenta and utilized as a membrane component.…”
Section: Other Metabolites Altered In the Fetal Muscles Of The Ln Groupmentioning
confidence: 99%